Urban Spatial Structure, Employment and Social Ties: European versus American Cities - Pierre M. Picard; Yves Zenou (Institute for the Study of Labor (IZA), 2015)
We develop a model where workers both choose their residential location (geographical space) and their social interactions (social space). In equilibrium, we show under which condition some individuals reside close to the job center while others live far away from it. Even though the two populations have the same characteristics and no group experiences any discrimination, we show that the majority group always has a lower unemployment rate than the minority group both when ethnic minorities reside close and far away from the city-center where jobs are located. This is because they have a larger and better-quality social network. This result is quite unique as it can explain the high unemployment rates of ethnic minorities both in European and American cities.
Keywords: A14; J15; R14; Z13; 330; social interactions; segregation; labor market; spatial mismatch; network size